Research on data transmission of wireless sensor networks based on symmetric key algorithm - Zhou, Wei; Li, Ping; Wang, QinJu; Nabipour, Narjes (Measurement : journal of the International Measurement Confederation, 2020)
•The decryption algorithm is used to decrypt the ciphertext.•Using penalty function to optimize node energy consumption during data transmission.•Improving the security and data transmission efficiency of wireless sensor. In order to improve the security and transmission efficiency of data transmission of wireless sensor networks, data transmission of wireless sensor networks based on symmetric key algorithm has been studied. Through detailed analysis of the communication model, it is found that the decryption mainly distributes the decryption password and obtains the decrypted secret key. The secret key and the ciphertext are grouped by the decryption function to finally obtain the ciphertext. The decryption algorithm is used to decrypt the ciphertext to realize the secure processing of the wireless sensor networks data. Also, experimental analysis shows that the minimum time required for the decryption and encryption of this method is 0.046 ms and 2.146 ms when the key length is 16. When adopting this method, the wireless sensor networks have high transmission quantity and long survival time, and the reliability of the transmitted data is up to 98.6%.